Propagación de cinco especies forestales nativas en proceso de extinción, utilizando tres sustratos, en la comunidad Chazojuan cantón Echeandia, provincia Bolívar - Carvajal Granizo, Ariel Lautaro (2015)
The forests, especially the natives, constitute natural resources of great importance, they control the erosion and they provide wood, seeds and other products for different uses, only the function of the forest like wooden producer is taken into account, reason why you deforesting the forests until draining the resource, causing erosion problems, diminishing the fertility of the floor and limiting the possibility of gathering of fruits and seeds with ends of propagation of the species. This investigation was carried out in the community Chazojuan, canton Echeandía, county of Bolívar, to an altitude of 1042 msnm, with a temperature average of 24 oC and an annual precipitation of 2700 mm. The objectives that thought about were: a) Spread five native forest species in extinction process, using three bases, in the community Chazojuan. b) Determine the morphological characteristics that it presents each a of the forest species. c) Evaluate in which of the bases the plant obtains bigger development. d) Carry out an economic analysis relationship benefit-cost, B/C. a design of Complete Blocks was used at random in factorial arrangement 5 x 3 with three repetitions. The Factor A it corresponded to 5 forest species: A1 = Fernán Sánchez; A2 = Aliso; A3 = white Cedar; A4 = red Cedar and A5 = Language cow. The Factor B was three types of bases: B1 = Earth common 50% + fuzz of rice 50%; B2 = Earth common 50% + fuzz of coffee 50% and B3 = Earth common 50% + earth of mountain 50%. Fifteen treatments were had. Chemical analysis of the bases was made, variance analysis, test of Tukey to 5%, correlation analysis and regression and economic analysis of the relationship benefice/cost. The handling of the rehearsal was made with good practical Agronomic. The most outstanding results obtained in this investigation were: Highly significant statistical differences existed in all the valued variables as effect of the main factors and interactions. The species forest Alder one had a with 100% of survival of the plants. The highest percentages in survival of the plants to the 120 days later der the siembra for the types of bases registered in the B2: Earth common 50% + fuzz of coffee 50% with 96,50%. In the interaction of factors, the highest percentage of survival in plants to the 120 days, was evaluated in the T4: I plane + Earth common 50% + fuzz of rice 50% 104(A2B1); T5: I plane + Earth common 50% + fuzz of coffee 50% (A2B2) and T6: I plane + Earth common 50% + earth of mountain 50% (A 2B3) with 100%. The independent variables that contributed to obtain a percentage of survival of plants to the 120 days were: days to the germination, height of plants to the 90 days, diameter of the shaft to the 90 days and number of leaves to the 120 days. The independent variable that had a correlation significant negative with the percentage of on vivencia of plants it was the incidence of Minador of the leaf (Liriomyza trifolii). Only taking in consideration the economic thing, the best relationship benefits cost it was given in the T5: I plane + Earth common 50% + fuzz of coffee 50% (A2B2) with a value of 4,00; this means that the viverista for each overturned dollar has a gain of $. 0,25. This study contributed to improve the sexual propagation of the forest species Fernán Sánchez; I Plane; white Cedar and Cedar colored in terms of obtaining plants of good quality, very developed and in smaller time, that makes more competitive the activity of the dedicated viverista to the production of forest plants in extinction danger